Left Ventricular Dyssynchrony in Acute ST Elevated Myocardial Infarction in Patients with Normal QRS duration (Bangladesh Heart Journal, 2016)
Background: The aim of this study was to assess left ventricular dyssynchrony after acute ST elevated myocardial infarction (STEMI) in patients with normal QRS duration. Real time 3D echocardiography (RT3DE) with triplane tissue synchronization imaging (TSI) used to identify segmental left ventricular systolic velocity in ejection phase to evaluate LV dyssynchrony in patients with STEMI and the findings were compared with control.Materials and methods: RT3DE with triplane TSI was performed within 4 days of AMI after thrombolysis or primary PCI in 31 patients and compared with 31 agematched controls. Regional myocardial velocities were assessed in 12 segments in ejection phase, and the corresponding time to peak systolic velocity (Ts) was measured. To assess LV dyssynchrony Ts-4, Ts-6, Ts- SD-6, Ts-12 and Ts-SD-12 were computed by offline dedicated software semi-automatically.Results: The dyssynchrony parameters were significantly prolonged in patients with AMI. Among the dyssynchrony parameters TS-SD-12 was better indicator of LV dyssynchrony. The Ts-SD-12 was significantly prolonged in the STEMI group when compared with controls. In patients with acute STEMI mean Ts-SD-12 was 43.2±19.1 milliseconds whereas in control group it was 23.0 ±6.5 milliseconds (p